“Diagnóstico en la estación de bombeo “El Carrizal” de la planta potabilizadora de agua Bellavista del cantón Salcedo periodo 2015. Propuesta de implementación de un sistema SCADA en mejora de la toma de decisiones en cuanto a la captación y distribución de agua potable” - Jijón Cando, Pedro Fernando (2016)
The present work focuses on carrying out a diagnosis in the "El Carrizal" water pumping station of the Bellavista water treatment plant of the Salcedo canton in order to know all the weaknesses that the plant and station currently have, the population has difficulties with the drinking water service not due to water shortages, it is due to the deficient use of the vital liquid, currently the water arrives at certain hours in the different neighborhoods of the canton, the main problem in the pumping station and the potabi plant lizadora is in the lack of automation in the entire process from the beginning to the end, there is waste of water, pumping is done only for 9 hours a day.